INTESTINAL MYIASIS (MAGGOT INFESTATION OF INTESTINES) - Noor, Noor Ahmad (Journal of Ayub Medical College Abbottabad, 1988)
Infection with maggots or fly larva are seen all over the world and results from invasion of tissues and organs by the larvae of various species of flies like Musca, Fannia, Chrysinia and Calliphora. Myiasis can involve skin, eyes, connective tissues, nasopharynx, intestines and urethra. Intestinal myiasis, a rare clinical entity results from ingestion of food contaminated with the eggs or larvae of flies, some of which survive passage through the stomach and later mature in the intestines before they are passed in the stools. Intestinal myiasis, sometimes results from deposition of larvae by the flies round the anus of the patient and such larvae may crawl into the rectum to complete their feeding inside the body. Children are particularly vulnerable to myiasis due to their out-door exposure or ingestion of fly contaminated food. Published reports about intestinal myiasis from this part of the world are scanty because unless maggots are seen by the physician himself diagnosis cannot be made. During the last five years two well documented cases of this condition were diagnosed and treated by the author, the summary of these is as under: